If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 = 6 + 2x Solving 22 = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 22 + -2x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 22 + -2x = 6 + 0 22 + -2x = 6 Add '-22' to each side of the equation. 22 + -22 + -2x = 6 + -22 Combine like terms: 22 + -22 = 0 0 + -2x = 6 + -22 -2x = 6 + -22 Combine like terms: 6 + -22 = -16 -2x = -16 Divide each side by '-2'. x = 8 Simplifying x = 8
| k+4/2=k+9/2 | | (5x+4)(x-1)=2 | | k+4/2=k+9/4 | | -7x+2+4x=2 | | 40=12x+4 | | 2x-x+3+3x=x+13 | | -7x+2+5x=2 | | 6x^2+5x=-1 | | (2x-5)/3=(2-5x)/7 | | 22+x=12 | | 4(2x-8)=1/7(49x+70) | | 37g^8-37h^8= | | 19+x=2 | | x+x+16+3x=211 | | x^3+4x^2=7x+28 | | 1+2x+2x=49 | | 733=P(1+0.01)3 | | A=P(1+r)N | | 1/3x-15=18 | | 22=6f-8 | | -6=-1 | | -30+7x=26+3x | | 1-x=2(0,5-0,5x) | | 7x+8+x=-24 | | x^8-3x^7=x^6-3x^5 | | (d-4/4)^2=16 | | 4x+4(x-18)=-8 | | -42=-18+6c | | -5t-5/-10=70 | | x(x+14)=(x+7)(x+7) | | 28+9x=-20+11x | | x(3-x^2)=0 |